Identifying the building blocks of plant-based meat analogue industry : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Palmerston North, New Zealand. EMBARGOED until 1 March 2027. - Rennie, Kizzy (Massey University, 2022)
Concerns of population growth, climate change and food shortage have tasked the food industry with finding realistic solutions to global issues. Human consumption, an intersection of all three factors, is affected by social, economic, and scientific circumstances. Animal protein contributes to almost half of all protein eaten by humans. Therefore, implementation of sustainable meat consumption requires the food industry to discover new protein substitutes with the potential to shift dietary customs. The present plant-based meat analogue market was investigated to determine the economic status and societal impact to be considered when manufacturing alternative meat products. North America and Europe, also the largest per capita consumers of meat, emerged as key players for manufacture and export. Australia was identified as the fastest growing region with access to both international merchandise and regional technology. Israel, which has developed an impactful 3D technology hub, is leading the 4.0 generation of food technology. The Covid-19 pandemic and Russian-Ukraine war accelerated health and environment concerns among consumers. As a result, eco-centric consumers desire products which are more natural and less processed. Plant-based clientele are driven by realistic taste, appearance, and format. Stock data showed a growing interest in alternatives, specifically shifting from beef to chicken. However, due to the vast nature of the industry, there is opportunity to dominate submarkets. A meat alternative was designed using novel shear processing to structure soy protein isolate (SPI), pea protein isolate (PPI), wheat gluten (WG) and deheated mustard powder (DMP). Rheological measurements determined that raw soy and pea pastes elicited similar responses to shear and temperature and are complementary under HTSP conditions. The effect of different wheat increments (5-25%) resulted in a firmer, spongier analogue but disrupted SPI and PPI interactions when compared to the control (70:30 PPI:SPI). This led to conflicting TA and solubility values. Meat analogues contained more protein than cooked chicken but less extensive cross linking and protein to protein interactions, especially DMP20, which produced the closest average textural values to chicken (C=9.51:8.31 G=11.50:17.12). The DMP formulation can be improved with colour and flavour considerations. However, further studies on nutritive quality and microstructure analysis will determine the commercial viability of the product design.
Embargoed until 1 March 2027
Keywords: 300607 Food technology